Ceria–Zirconia Particles Wrapped in a 2D Carbon Envelope: Improved Low‐Temperature Oxygen Transfer and Oxidation Activity. (8th October 2015) - Aneggi, Eleonora; Rico‐Perez, Veronica; de Leitenburg, Carla; Maschio, Stefano; Soler, Lluís; Llorca, Jordi; Trovarelli, Alessandro
Abstract: Engineering the interface between different components of heterogeneous catalysts at nanometer level can radically alter their performances. This is particularly true for ceria‐based catalysts where the interactions are critical for obtaining materials with enhanced properties. Here we show that mechanical contact achieved by high‐energy milling of CeO2 –ZrO2 powders and carbon soot results in the formation of a core of oxide particles wrapped in a thin carbon envelope. This 2D nanoscale carbon arrangement greatly increases the number and quality of contact points between the oxide and carbon. Consequently, the temperatures of activation and transfer of the oxygen in ceria are shifted to exceptionally low temperatures and the soot combustion rate is boosted. The study confirms the importance of the redox behavior of ceria‐zirconia particles in the mechanism of soot oxidation and shows that the organization of contact points at the nanoscale can significantly modify the reactivity resulting in unexpected properties and functionalities. Abstract : Rußverbrennung : Der enge Kontakt von Ceroxid‐ und Zirkoniumoxid‐Partikeln in einer dünnen Kohlenstoffschicht fördert den Transfer von Gitter‐ und Oberflächensauerstoffatomen. Dadurch wird die Oxidationstemperatur für die Rußverbrennung deutlich abgesenkt (siehe Bild).